AB0874 Mental health disorders in patients with axial spondyloarthritis: increasing our understanding of the disease. results from the atlas-2017. (12th June 2018) - Garrido-Cumbrera, M.; Navarro-Compan, V.; Gálvez-Ruiz, D.; Delgado-Dominguez, C.; Font Ugalde, P.; Braçe, O.; Zarco, P.; Chacón-García, J.; Plazuelo-Ramos, P.
Abstract : Background: Depression and other mental disorders are among the most prevalent comorbidities in patients with axial spondyloarthritis (axSpA). Objectives: To assess the association between sociodemographic characteristics, disease progression, and mental health comorbidity with risk of mental disorders (RMD). Methods: In 2016 a sample of 680 axSpA patients was interviewed as part of the Spanish Atlas. To quantify the RMD, GHQ-12 scale was employed. Possible RMD predictors taken into account in the analysis were: sociodemographic characteristics (age, gender, being part of a couple, patient association membership, job status); disease characteristics (BASDAI, spinal stiffness, functional limitation in 18 daily activities; and mental health comorbidities. All clinical variables showed a Cronbach's alpha coefficient guaranteeing the reliability of the scales used. First, a descriptive analysis was employed to describe the sample and study variables. Second, univariate correlation and homogeneity analyses between each predictor (independent variable) and RMD (GHQ-12) were performed. Results: All variables except educational level and thoracic stiffness showed significant univariant correlation with RMD. BASDAI, functional limitation and age showed higher coefficient (r=0.543, p<0.001; r=0.378, p<0.001; r=−0.174, p<0.001, respectively). Multiple hierarchical regression analysis showed as sociodemographic variables explained in great detail the RMD (R 2= 83.2%). By contrast, having established sociodemographic as a control variable, the inclusion of depression and anxiety to the model increased the R 2 value to just 0.6% (p < 0.001), while the inclusion of variables related to the disease characteristics add 5.5% (p < 0.001) to the GHQ-12 punctuation variability. The only variables presenting a significant coefficient different from 0 were BASDAI (0.52, p < 0.001) and functional limitation (0.14, p < 0.01). This suggests that once the sociodemographic and mental commorbidity variables are established, a change in BASDAI levels or functional limitation impacts the GHQ-12 score. In the stepwise regression analysis, four variables (BASDAI, functional limitation, association membership, cervical stiffness) showed a significant relation to GHQ-12 and explained the majority of RMD variability. BASDAI displayed the highest explanatory degree (R 2 =0.875, p<0.001). Conclusions: In axSpA, patients at certain sociodemographic levels are more prone to present a higher BASDAI. Taking these conditions for granted, the degree of disease progression measured by BASDAI is a good indicator of RMD. Therefore, in those patients with higher disease activity, psychiatric evaluation and intervention should be considered within the medical treatment. Acknowledgements: The Atlas was promoted by CEADE and funded by Novartis Disclosure of Interest: None declared